PERAMALAN DAYA LISTRIK BERDASARKAN JUMLAH PELANGGAN PLN MENGGUNAKAN MODEL FUNGSI TRANSFER DENGAN OUTLIER (Studi Kasus di PT PLN (Persero) Rayon Semarang Selatan) - Retza Bahtiar Anugrah; Sudarno Sudarno; Budi Warsito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Electrical energy is one of the components of Gross Domestic Product which able to stimulate the economic matter because it has been becoming a primary needs in the society. In order to meet the growing electrical energy, State-Owned Enterprises (SOEs) need to develop systems and proper planning. It needs a forecasting of electric power based on customer to meet a sufficient electricity supply. This study aims to predict the electrical power by electric customers using transfer function model with outliers. The use of transfer function model is intended to determine the role of power users that have an impact on the electric power. One of the stages of modeling the transfer function is to set the order of the transfer function parameters, they are b, r, and s. And by modeling the outlier is useful to eliminate the effect of outliers itself. The analysis and discussion show that based on the AIC value, the best model is the transfer function model by weighting the impulse response of the parameter that is ω_0 = 55,55652 and the noise series model of the transfer function is ARIMA (1,0,1) with 8 outliers. The details of the outliers consist of one Additive Outliers type in the 33rd and seven Level Shift Outliers in the 14th, 31st, 9th, 10th, 21st, 22nd and 58th. Size forecasting accuracy using MAPE value 19.77%. Keywords: Transfer function, outliers, ARIMA, electrical power, AIC, MAPE